THE IMPLEMENTATION OF AN ERP IN A PUBLIC UNIVERSITY: THE CASE OF THE UNIVERSITY OF GUANAJUATO (JÓVENES EN LA CIENCIA, 2018)
The Enterprise Resource Planning Systems have become a very useful tool in companies in recent years, even universities are beginning to implement this type of systems, however educational institutions have presented some challenges in their implementation, for this it is necessary to know what are the critical success factors that facilitate the implementation of an ERP in a Higher Education Institution. A questionnaire was developed for the present study which was sent to different characters involved with the ERP of the University of Guanajuato, in order to find out what the conditions of its implementation were and also to determine what actions can be taken to improve its functioning. The research is still ongoing but some data found in the responses of the participants has been that not all users of the platform were aware of the use of the tool when it was implemented, however the interaction among those who use the ERP in The University of Guanajuato is giving rise to the knowledge management that in turn can lead to improve its application.
Keywords: Array; Array; Array; Array